2007
DOI: 10.3200/gntp.168.3.323-360
|View full text |Cite
|
Sign up to set email alerts
|

Taking the First Step Toward a Moral Action: A Review of Moral Sensitivity Measurement Across Domains

Abstract: Moral sensitivity is the first component of the 4-component moral action process (J. R. Rest, 1986). The author reviews moral sensitivity operationalization and measurement across multiple samples and domains. She reviews 3 definitions of the construct (i.e., recognition and affective response, recognition, and recognition and ascription of importance) and measurement instruments based on these definitions and assesses these instruments according to their methodological rigor. The author also briefly discusses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
64
0
6

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(72 citation statements)
references
References 80 publications
2
64
0
6
Order By: Relevance
“…First, our concept of basic moral sensitivity, developed from our readings of social-cognitive domain theory (Nucci, 2001;Turiel, 1983), the four-component model of moral functioning and its concept of moral sensitivity (Jordan, 2007;Narvaez & Rest, 1995;Rest, 1985), and the social cognition approach to moral development (Arsenio & Lemerise, 2004;Hoffman, 2000;Narvaez & Lapsley, 2005), is a new construct measured with only three items. Although the findings indicate the importance of the concept, further empirical and theoretical work is needed to elaborate the concept and the measurement of it, and to test it further.…”
Section: Discussionmentioning
confidence: 99%
“…First, our concept of basic moral sensitivity, developed from our readings of social-cognitive domain theory (Nucci, 2001;Turiel, 1983), the four-component model of moral functioning and its concept of moral sensitivity (Jordan, 2007;Narvaez & Rest, 1995;Rest, 1985), and the social cognition approach to moral development (Arsenio & Lemerise, 2004;Hoffman, 2000;Narvaez & Lapsley, 2005), is a new construct measured with only three items. Although the findings indicate the importance of the concept, further empirical and theoretical work is needed to elaborate the concept and the measurement of it, and to test it further.…”
Section: Discussionmentioning
confidence: 99%
“…Dans les différentes études recensées par Jordan (2007), l'auteure met en évi-dence la difficulté pour les chercheuses et chercheurs d'établir un consensus quant aux critères de construction d'une vignette à respecter afin qu'elle soit valide, qu'elle présente une plausibilité dans le domaine visé et qu'elle mesure précisément la sensibilité à l'éthique ou encore la reconnaissance des dimensions dans un problème éthique. La majorité des études recensées (Jordan, 2007) ont adopté une approche quantitative.…”
Section: Discussion Sur La Méthodologieunclassified
“…La majorité des études recensées (Jordan, 2007) ont adopté une approche quantitative. Nous avons plutôt opté pour une approche qualitative dans notre recherche étant donné que nous visions une certaine souplesse et une exploration plus approfondie des réflexions des participantes devant un problème éthique à l'école.…”
Section: Discussion Sur La Méthodologieunclassified
See 1 more Smart Citation
“…A 2007 review 88 of moral sensitivity research reported a paucity of well-validated tools and a lack…”
mentioning
confidence: 99%